2022
DOI: 10.1093/stcltm/szac002
|View full text |Cite
|
Sign up to set email alerts
|

The Crosstalk Between Adipose-Derived Stem or Stromal Cells (ASC) and Cancer Cells and ASC-Mediated Effects on Cancer Formation and Progression—ASCs: Safety Hazard or Harmless Source of Tropism?

Abstract: Adipose-derived stem or stromal cells (ASCs) possess promising potential in the fields of tissue engineering and regenerative medicine due to their secretory activity, their multilineage differentiation potential, their easy harvest, and their rich yield compared to other stem cell sources. After the first identification of ASCs in humans in 2001, the knowledge of their cell biology and cell characteristics have advanced, and respective therapeutic options were determined. Nowadays, ASC-based therapies are on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 139 publications
(181 reference statements)
0
9
0
Order By: Relevance
“…In addition, ASCs/MSCs are capable of modulating the metabolism of breast cancer cells by stimulating, for example, the upregulation of cluster of differentiation 36 (CD36), a fatty acid receptor, leading to an increased proliferation rate [ 113 ], or the upregulation of S100 calcium-binding protein A7, involved in cell cycle regulation [ 114 ]. Moreover, numerous studies demonstrate that cancer cells are able to educate ASCs/MSCs, resulting in an altered gene and protein expression [ 143 ]. The interaction with cancer cells increased the release of tumor-promoting cytokines such as CCLs, CXCLs, SDF, and EGF [ 105 , 117 ]; angiogenesis factors including VEGF, angiopoietins, EGF, galectin-1, IGF1, and keratinocyte growth factor (KGF) [ 102 , 115 , 118 , 144 ]; and EMT inducers such as TGFβ, platelet-derived growth factor D (PDGF-D), and stem cell factor (SCF) [ 106 , 118 , 145 ].…”
Section: Mutual Interaction Between Ascs/mscs and Breast Cancer Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, ASCs/MSCs are capable of modulating the metabolism of breast cancer cells by stimulating, for example, the upregulation of cluster of differentiation 36 (CD36), a fatty acid receptor, leading to an increased proliferation rate [ 113 ], or the upregulation of S100 calcium-binding protein A7, involved in cell cycle regulation [ 114 ]. Moreover, numerous studies demonstrate that cancer cells are able to educate ASCs/MSCs, resulting in an altered gene and protein expression [ 143 ]. The interaction with cancer cells increased the release of tumor-promoting cytokines such as CCLs, CXCLs, SDF, and EGF [ 105 , 117 ]; angiogenesis factors including VEGF, angiopoietins, EGF, galectin-1, IGF1, and keratinocyte growth factor (KGF) [ 102 , 115 , 118 , 144 ]; and EMT inducers such as TGFβ, platelet-derived growth factor D (PDGF-D), and stem cell factor (SCF) [ 106 , 118 , 145 ].…”
Section: Mutual Interaction Between Ascs/mscs and Breast Cancer Cellsmentioning
confidence: 99%
“…Recently, increasing evidence highlights that ASCs/MSCs are educated and de-differentiated by cancer cells and the TME, fueling malignancy and therapy resistance [ 226 , 227 ]. Cancer-cell-secreted factors and direct cancer cell–ASC/MSC contacts induce a pro-tumorigenic population of ASCs/MSCs, named cancer-associated MSCs (CA-MSCs) [ 143 ]. CA-MSCs have the ability to differentiate into multiple cell lineages, such as fibroblasts and adipocytes, suggesting that MSCs may play a key role in the generation of most stromal components of the TME.…”
Section: Mutual Interaction Between Ascs/mscs and Breast Cancer Cellsmentioning
confidence: 99%
“…Thus, the data to date regarding the influence of tamoxifen on ASC are limited and partly very controversial. In particular, conflicting data regarding the role of ASC in cancer progression were reported, showing that in in vivo and in vitro experiments, ASC favored tumor growth and increased extracellular matrix deposition and vascularization [ 49 ]. On the one hand, some studies investigated the effect of tamoxifen in vitro on ASC and demonstrated that tamoxifen concentrations above 2 µM had cytotoxic effects on ASC in terms of apoptosis induction and proliferation inhibition [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the effect of tamoxifen on ASC, the interaction between ASC and mammary carcinoma cells has also been extensively studied. Overall, conflicting evidence emerged during recent years about the safety profile of ASC applications as ASC may induce tumor progression and invasion [ 49 ]. In this respect, it is still unclear whether preadipocytes act differently from mature adipocytes [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation